2019
DOI: 10.1101/712752
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ovarian hormones mediate the prophylactic efficacy of (R,S)-ketamine and (2R,6R)-hydroxynorketamine in female mice

Abstract: Number of words in the abstract: 227 (250 max)Number of words in the text: 3812 (4000 max) ABSTRACT BACKGROUND: Females are more likely than males to develop major depressive disorder (MDD) after exposure to stress. We previously reported that the administration of (R,S)-ketamine before stress can prevent stress-induced depressive-like behavior in male mice but have yet to assess efficacy in female mice or for other compounds, such as the metabolites of (R,S)-ketamine. METHODS:We administered (R,S)-ketamine or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Although the initial findings demonstrating antidepressant-relevant biological activity of ( 2R,6R )-HNK have been widely replicated and expanded upon by a number of independent research groups (Bonaventura et al, 2022; Cavalleri et al, 2018; Chen et al, 2018; Chou et al, 2018; Collo et al, 2018; Fred et al, 2019; Fukumoto et al, 2019; Pham et al, 2018; Wray et al, 2018; Yao et al, 2018; Ye et al, 2019), (2 R, 6 R )-HNK is one of the major brain metabolites of ( R,S )-ketamine, but its antidepressant-like activity and contribution to the actions of the parent drug has been contested (Abdallah, 2017; Collingridge et al, 2017; Zanos et al, 2017). We previously showed that a systemic or intra-cortical administration of ( 6 )-HNK displayed similar sustained antidepressant-like behavioral actions to those of ( R,S )-ketamine (i.e., at 24 hours post-injection (t24h)) when assessed using the forced swim test (FST).…”
Section: Introductionmentioning
confidence: 99%
“…Although the initial findings demonstrating antidepressant-relevant biological activity of ( 2R,6R )-HNK have been widely replicated and expanded upon by a number of independent research groups (Bonaventura et al, 2022; Cavalleri et al, 2018; Chen et al, 2018; Chou et al, 2018; Collo et al, 2018; Fred et al, 2019; Fukumoto et al, 2019; Pham et al, 2018; Wray et al, 2018; Yao et al, 2018; Ye et al, 2019), (2 R, 6 R )-HNK is one of the major brain metabolites of ( R,S )-ketamine, but its antidepressant-like activity and contribution to the actions of the parent drug has been contested (Abdallah, 2017; Collingridge et al, 2017; Zanos et al, 2017). We previously showed that a systemic or intra-cortical administration of ( 6 )-HNK displayed similar sustained antidepressant-like behavioral actions to those of ( R,S )-ketamine (i.e., at 24 hours post-injection (t24h)) when assessed using the forced swim test (FST).…”
Section: Introductionmentioning
confidence: 99%